Changes in EU Legislation and New Operational Requirements on Infrastructure Managers in the Czech Republic in Relation to Public Sidings - Matuška, Jaroslav; Matuška, Jaroslav; Nachtigall, Petr; Šourek, David; Široký, Jaromír; Ježek, Jindřich (Scientific Research Center Ltd., 2018)
This paper deals with railway legislation with respect to railway transport in the Czech Republic and EU. It describes certain changes in legislation and their impact on infrastructure managers. It mainly focuses on the tasks infrastructure managers have to take on in relation to a new railway category – public sidings. The authors also deal with recent experience with the proces of allocating rail capacity on public sidings.
Změny legislativy EU a nové provozní požadavky na manažery infrastruktury veřejně přístupných vleček v ČR
Keywords: infrastructure manager; legislation; public siding; railway undertaking; railway transport; provozovatel dráhy; legislativa; veřejně přístupná vlečka; železniční dopravce; železniční doprava